A study of how clasroom group dynamics affect second language acquisition and learning in a bilingual setup: a case of lower Gweru secondary schools. - Gundani, Lena Vongai (Midlands State University, 2018)
The choice of the research topic was influenced by personal interest in the field of linguistics. The aim of the study was to highlight How classroom group dynamics affect second language acquisition and learning in a bilingual setup. It presents the factors that affect quality contact and quantity contact between groups in the classroom. Different theoretical constructs were applied in the discussion of the research topic and this includes Schumman’s Acculturation theory. Two schools were used as a sample. Random sampling was used which resulted in a sample of forty students, eight teachers and two HODs. The data collected proved beyond reasonable doubt that factors like social dominance, enclosure and cohesiveness and size affect quality and quantity contact between groups. The results also revealed that the teacher has power to influence quality and quantity contact between groups by employing teaching strategies which include cooperative learning methods, group work, pair work, avoiding rigid sitting positions among others. The study also recommends that teachers should exercise equality among students so that all forms of dominance are eradicated. Cohesiveness should be maintained to ensure that there is quality interaction between students in the classroom to facilitate second language acquisition and learning. This study of classroom group dynamics highlights other important factors which affect second language acquisition in a classroom set up which are often overlooked. The research also highlights how a second language support system can be developed in a classroom by enhancing quality and quality contact